The effect of sleep duration on hemoglobin and hematocrit: observational and Mendelian randomization study. Issue 7 (8th January 2020) - Wang, Jiao; Kwok, Man Ki; Au Yeung, Shiu Lun; Li, Albert Martin; Lam, Simon; Leung, Gabriel Matthew; Schooling, Catherine Mary
Abstract: Study Objective: Observationally sleep duration is positively associated with hemoglobin (Hgb), whether this association is causal and consistent by sex remains unclear. Here, we assessed the association of sleep duration with Hgb and hematocrit (Hct) observationally in late adolescence in a population-representative Chinese birth cohort "Children of 1997" with validation using Mendelian randomization (MR) in adults. Methods: In the "Children of 1997" birth cohort (recruited = 8327, included = 3144), we used multivariable linear regression to assess the adjusted associations of sleep duration (measured as time in bed) with Hgb and Hct at 17.5 years and any sex differences. Using two-sample MR, we assessed the effect of sleep duration on Hgb and Hct, based on 61 single nucleotide polymorphisms (SNPs) applied to genome-wide association studies of Hgb and Hct in adults ( n = 361 194). Results: Observationally, self-reported sleep duration was positively associated with Hct (0.034 standard deviations [ SD s] per hour, 95% confidence interval [CI] 0.019 to 0.049), but not with Hgb. Using MR longer sleep increased Hct (0.077 SD per hour, 95% CI 0.035 to 0.119) and Hgb (0.065 SD per hour, 95% CI 0.020 to 0.109) using Mendelian randomization pleiotropy residual sum and outlier (MR PRESSO), with more pronounced associations in men. Conclusions: Our novel findings indicate sleep increases both Hgb and Hct, particularly in men, perhaps contributing to its restorative qualities. Potential difference by sex and the implications of these findings warrant investigation.